Wasp venom from Vespa magnifica acts as a neuroprotective agent to alleviate neuronal damage after stroke in rats. (31st December 2022) - Zhao, Hairong; Wang, Mei; Huang, Xi; Wu, Xiumei; Xiao, Huai; Jin, Fanmao; Lv, Jiaming; Cheng, Jidong; Zhao, Yu; Zhang, Chenggui
Abstract: Context: Acute ischaemic stroke (AIS) is a major cause of disability and death, which is a serious threat to human health and life. Wasp venom extracted from Vespa magnifica Smith (Vespidae) could treat major neurological disorders. Objective: This study investigated the effects of wasp venom on AIS in rats. Material and methods: We used a transient middle cerebral artery occlusion (MCAO) model in Sprague-Dawley rats (260–280 g, n  = 8–15) with a sham operation group being treated as negative control. MCAO rats were treated with wasp venom (0.05, 0.2 and 0.6 mg/kg, i.p. ) using intraperitoneal injection. After treatment 48 h, behavioural tests, cortical blood flow (CBF), TTC staining, H&E staining, Nissl staining, TUNEL assay, immunohistochemistry (IHC) and ELISA were employed to investigate neuroprotective effects of wasp venom. Results: Compared with the MCAO group, wasp venom (0.6 mg/kg) improved neurological impairment, accelerated CBF recovery (205.6 ± 52.92 versus 216.7 ± 34.56), reduced infarct volume (337.1 ± 113.2 versus 140.7 ± 98.03) as well as BBB permeability as evidenced by changes in claudin-5 and AQP4. In addition, function recovery of stroke by wasp venom treatment was associated with a decrease in TNF-α, IL-1β, IL-6 and inhibition activated microglia as well as apoptosis. Simultaneously, the wasp venom regulated the angiogenesis factors VEGF and b-FGF in the brain. Conclusions: Wasp venom exhibited a potential neuroprotective effect for AIS. In the future, we will focus on determining whether the observed actions were due to a single compound or the interaction of multiple components of the venom.